A Novel Approach for Self‐Care in Pregnant Women With Hypothyroidism: Mobile‐Based Development and Insights - Narges Mahdavi; Reza Safdari; Athena Behforouz; Nahid Ramezanghorbani (Health Science Reports, 2025)
ABSTRACT Background and Aim Hypothyroidism affects 2–3% of pregnant women. This study aims to develop a mobile self‐care program to enhance self‐management and health outcomes for these women. Methods The present study is a developmental and applied research that was conducted in three stages at the Yas Hospital's Women's Clinic and Pregnancy Care Center affiliated with Tehran University of Medical Sciences in 2023. In the first stage, the informative elements of the program were determined through a review of previous studies and a survey of 20 obstetricians and endocrinologists. In the second stage, a prototype of the mobile‐based application was developed. In the third stage, the designed application was evaluated by 10 medical informatics and technology specialists using Nielsen's standard usability questionnaire. The questionnaire results were analyzed using descriptive statistics and SPSS 16 software. Results In the first stage, 58 informative elements and 9 vital capabilities were identified for the self‐care application, and then the application was designed using Java programming language in two sections: user registration and main page, which includes medical information, medical records, tests, and reminders (doctor's appointments, medication and supplement intake, and laboratory tests). Overall, the usability test results of the self‐care application by experts showed that the usability of this application for pregnant women with hypothyroidism was evaluated at an acceptable level. Conclusions Mobile applications enhance awareness, improve health, and provide essential tools for disease management in pregnant women, reducing complications and benefiting the health of mothers and newborns.